Westonci.ca connects you with experts who provide insightful answers to your questions. Join us today and start learning! Discover comprehensive solutions to your questions from a wide network of experts on our user-friendly platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
Answer:
C. Both
Step-by-step explanation:
-7(-2) + 3(-4) = 2
14 + (-12) = 2
14 - 12 = 2
2 = 2
-7(1) + 3(3) = 2
-7 + 9 = 2
2 = 2
Both
C. Both
Step-by-step explanation:
-7(-2) + 3(-4) = 2
14 + (-12) = 2
14 - 12 = 2
2 = 2
-7(1) + 3(3) = 2
-7 + 9 = 2
2 = 2
Both
B
Evidence:
If you plug in the order pair values they equal 2
Step 1:-7(-2)+3(-4)=2
Step 2:14-12=2
Step 3: 2=2
Evidence:
If you plug in the order pair values they equal 2
Step 1:-7(-2)+3(-4)=2
Step 2:14-12=2
Step 3: 2=2
We hope this was helpful. Please come back whenever you need more information or answers to your queries. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.